Modeling and characterization of ion-imprinted polymer for arsenic species removal from aqueous solution - Nurlin, Abu Samah (John Wiley & Sons, Inc., 2025)
Arsenic (As) contamination is a global issue, especially in As-rich geological formations. In this study, an ion-imprinted polymer (As(III)-IIP) is synthesized and characterized in terms of kinetic modeling and application via solid phase extraction (SPE). As is detected by using the inductively coupled plasma-mass spectrometer (ICP-MS). The surface study is also included in this study, in which the differences between non-imprinted polymer (NIP) and As(III)-IIP before and after sorption are observed via field electron scanning electron microscope (FESEM). As a result, As(III)-IIP follows the pseudo-second-order of reaction in kinetics and reaches 95% within 5 min of removal. In FESEM micrographs, As(III)-IIP shows the particles on the surface are likely homogenous compared to NIP. Whereas As(III)-IIP after sorption is much more likely bigger than the original As(III)-IIP due to the expansion of particles during agitation in an aqueous solution. In the first cycle, 99.53% ± 0.45% of removal in real wastewater analysis is obtained via SPE. However, for the second cycle onwards, the removal is not removed totally, which shows that a new combination of eluent is required. In conclusion, As(III)-IIP shows good potential as a sorbent to be used for the removal of As from wastewater.